Advances in Flow Research - Engeser, Stefan; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
Since its discovery as a mental state in the 1970s, flow$1 (Bthe losing of oneself in productive activity$1 (Bhas become an important aspect of positive psychology and motivation research. Its processes have been studied in artists and athletes, applied to education and business, and explored in pursuits as varied as spirituality and internet use. As more analysis is done on optimal states of being, the more interest flow gathers as a focus of inquiry. In Advances in Flow Research, a panel of experts expands on Csikszentmihalyi$1 (Bs classic flow model and opens out key concepts. Contributors address ongoing questions regarding the conditions and components of flow, and consider various methods for measurement and assessment. Current findings are included on flow-related cognitive and personality issues, and the relation of flow to happiness and other affective states. And readers are introduced to emerging areas of study, including possible contributions of flow to negative behavior. Among the topics covered: Affective, cognitive, and performance-related consequences of flow. Psychophysiological correlates of flow experience. Understanding the autotelic personality. Integrating flow theory and cognitive evaluation theory. Flow in non-achievement situations. The dark side of flow. For social psychologists and researchers in flow and motivation, Advances in Flow Research fills a number of purposes: an up-to-date summary of what has been done, an idea book for new frontiers of inquiry, and a trove of useful references.s
- Historical lines and overview of current research -- A closer look at methodological approaches -- Factors predicting flow experience -- Flow, motivation and performance -- Flow in a non-achievement situation -- Flow as a feeling of oneness -- The dark side of the moon: negative aspects of Flow.-Neuropsychological correlates of flow experience -- Autotelic personality -- Theoretical integration and future lines.
Keywords: Philosophy (General).; Consciousness; Psychology; Personality and Social Psychology